Negative electrode slurry and preparation method and application thereof

By treating graphite with acid and combining with carboxymethylcellulose glue, an improved negative electrode slurry is formed, which solves the problem of poor circulation performance of existing graphite negative electrodes and achieves better circulation performance and capacity maintenance.

CN119812206APending Publication Date: 2025-04-11ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411930529.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The lithium-ion batteries made of existing graphite negative electrodes have poor circulation performance, mainly due to capacity loss caused by the damage and repair of the SEI film.

Method used

The negative electrode slurry is prepared by acid-treated graphite and carboxymethylcellulose glue to form a graphite surface containing oxygen-containing functional groups and nano-scale micropores. Combined with the use of glue solution A and glue solution B, the dispersion of graphite in the negative electrode slurry is improved.

Benefits of technology

By forming a structurally stable SEI film and providing new lithium storage sites, the circulation performance and first charge and discharge capacity of the lithium-ion battery are significantly improved, capacity loss is reduced, and the advantage of coated electrode sheets is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210175490000141
    Figure BDA0005210175490000141
  • Figure BDA0005210175490000151
    Figure BDA0005210175490000151
Patent Text Reader

Abstract

The invention discloses negative electrode slurry as well as a preparation method and application thereof. The negative electrode slurry comprises graphite subjected to acid treatment and a carboxymethyl cellulose glue solution, the carboxymethyl cellulose glue solution comprises a glue solution A and a glue solution B, the viscosity of the glue solution A is 500-4000 mpa.s, and the viscosity of the glue solution B is 7000-13000 mpa.s. The graphite in the negative electrode slurry is subjected to acid treatment, oxygen-containing functional groups (such as-CO,-COOH and the like) are formed on the surface of the graphite, and when the negative electrode slurry is applied to a secondary battery such as a lithium ion battery, the cycle performance of the material can be improved, and the first charge-discharge capacity of the material is improved. Meanwhile, by matching the glue solution A and the glue solution B, the dispersity of the graphite in the negative electrode slurry is improved, the appearance problems of black spots, particle aggregation, scratches and the like are not easy to occur in the slurry coating process, and the coated pole piece yield is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a negative electrode slurry and a preparation method and application thereof. Background Art

[0002] Lithium-ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of lithium ions between the positive and negative electrodes to work. + Insertion and deinsertion back and forth between the two electrodes: During charging, Li + The negative electrode is in a lithium-rich state after being deintercalated from the positive electrode and intercalated into the negative electrode through the electrolyte; the opposite is true during discharge. The negative electrode usually includes a negative electrode current collector and a negative electrode active material layer, among which graphite is one of the commonly used negative electrode active materials. However, the cycle performance of batteries made with conventional graphite negative electrodes is poor. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a negative electrode slurry, which is used in the preparation of negative electrodes of lithium ion batteries, and the resulting battery has good cycle performance.

[0004] The invention also provides a method for preparing negative electrode slurry.

[0005] The invention also provides a negative electrode active layer.

[0006] The invention also provides a negative electrode.

[0007] The invention also provides a secondary battery.

[0008] In a first aspect of the present invention, a negative electrode slurry is provided, comprising acid-treated graphite and carboxymethyl cellulose glue, wherein the carboxymethyl cellulose glue comprises glue A and glue B, the viscosity of glue A is 500 to 4000 mPa·s, and the viscosity of glue B is 7000 to 13000 mPa·s.

[0009] The negative electrode slurry according to the embodiment of the present invention has at least the following beneficial effects:

[0010] The graphite in the negative electrode slurry of the present invention is treated with acid to form oxygen-containing functional groups (such as -CO, -COOH, etc.) on the graphite surface, especially in the uneven surface areas (cracks, etc.). When the graphite is used in a secondary battery such as a lithium ion battery, these functional groups are + The first insertion forms a lithium carboxylate salt, which is conducive to the formation of a structurally stable SEI film, reducing the capacity loss caused by SEI film damage and repair during the material cycle, and improving the material's cycle performance. At the same time, acid oxidation can remove some of the defective structures in the resulting graphite negative electrode, thereby forming nanoscale micropores. These micropores are Li+ It provides new lithium storage sites and improves the initial charge and discharge capacity of the material. At the same time, with the combination of glue A and glue B, the dispersion of graphite in the negative electrode slurry is improved. During the slurry coating process, it is not easy to have appearance problems such as black spots, particle agglomeration, scratches, etc., and the coating rate of the electrode is high.

[0011] In some embodiments of the present invention, the viscosity of the glue A is 1000-3500 mPa·s, and the viscosity of the glue B is 8000-12000 mPa·s.

[0012] In some embodiments of the present invention, the degree of substitution Da of the carboxymethyl cellulose in the glue A is 0.6 to 0.8, such as 0.60 to 0.80.

[0013] Through the above implementation, carboxymethyl cellulose (CMC) with a low degree of substitution has good lipophilicity, has fewer polar functional groups on its surface, is more likely to be graphite-philic and infiltrate with graphite, the glue can have a good coating on the graphite, and the electrostatic repulsion between CMC will be stronger, thereby achieving the purpose of dispersing the slurry.

[0014] In some embodiments of the present invention, the degree of substitution Db of the carboxymethyl cellulose in the glue B is 0.8 to 1.2, such as 0.80 to 1.20.

[0015] In some embodiments of the present invention, the degree of substitution Da of carboxymethyl cellulose in the glue A and the degree of substitution Db of carboxymethyl cellulose in the glue B satisfy: Db=Da+0.3.

[0016] Through the above implementation, the combination of high and low degree of substitution carboxymethyl cellulose (CMC with low degree of substitution has better lipophilicity, is easier to infiltrate graphite, the glue has better coating on graphite, and the electrostatic repulsion between CMC will be stronger, thereby achieving the purpose of dispersing the slurry), the slurry can be dispersed more evenly, the particle size can be refined, and the electrode quality rate can be improved.

[0017] In some embodiments of the present invention, the mass fraction of carboxymethyl cellulose contained in the glue A is 1.5% to 3.5%, such as 1.9% to 2.4%.

[0018] In some embodiments of the present invention, the mass fraction of carboxymethyl cellulose contained in the glue B is 0.5% to 1.4%, such as 0.8% to 1.2%.

[0019] In some embodiments of the present invention, in the negative electrode slurry, the mass ratio of the glue A to the glue B is (3-7):(3-7).

[0020] In some embodiments of the present invention, in the negative electrode slurry, the weight ratio of graphite to carboxymethyl cellulose is (85-99):(0.5-3).

[0021] In some embodiments of the present invention, the acid used in the acid treatment includes at least one of carboxylic acid and carbonic acid.

[0022] In some embodiments of the present invention, the acid used in the acid treatment includes at least one of citric acid, oxalic acid, acetic acid, and carbonic acid.

[0023] In some embodiments of the present invention, the acid treatment step comprises: mixing graphite with an acid solution and stirring to obtain the acid-treated graphite.

[0024] In some embodiments of the present invention, the acid solution comprises an aqueous acid solution, specifically at least one of an aqueous citric acid solution, an aqueous oxalic acid solution, an acetic acid solution or an aqueous carbonic acid solution.

[0025] In some embodiments of the present invention, the mass ratio of the acid solution to graphite is (0.05-0.5):100, such as (0.1-0.15):100, and specifically 0.1:100.

[0026] In some embodiments of the present invention, the mass of the acid solution is 0.095% to 0.15% of the mass of the graphite.

[0027] In some embodiments of the present invention, in the acid solution, the acid concentration is 0.01-0.5 mol / L, such as 0.05-0.08 mol / L, specifically 0.06 mol / L.

[0028] In some embodiments of the present invention, the stirring time is 5 to 30 minutes, and the stirring speed is 100 to 500 rpm.

[0029] In some embodiments of the present invention, the glue A is prepared by a preparation method comprising the following steps:

[0030] Sa-1, mixing the fiber and an alcohol solvent, and mixing with an alkaline solution to obtain an alkalized fiber solution;

[0031] Sa-2, the alkalized fiber solution is mixed with chloroacetic acid, and the etherification reaction is carried out at 30-45°C for 10-30 minutes to obtain a glue solution A containing carboxymethyl cellulose.

[0032] In some embodiments of the present invention, in step Sa-2, the alkalized fiber solution is mixed with chloroacetic acid and subjected to etherification reaction at 30-42° C. for 10-25 min to obtain a glue solution A containing carboxymethyl cellulose.

[0033] In some embodiments of the present invention, step Sa-2 includes: mixing the alkalized fiber solution with chloroacetic acid, performing an etherification reaction at 30-45° C. for 10-30 minutes to generate carboxymethyl cellulose, and adding solvent water to the obtained glue system to obtain glue A containing carboxymethyl cellulose.

[0034] In some embodiments of the present invention, the glue solution B is prepared by a preparation method comprising the following steps:

[0035] Sb-1, mixing the fiber and an alcohol solvent, and mixing with an alkaline solution to obtain an alkalized fiber solution;

[0036] Sb-2, the alkalized fiber solution is mixed with chloroacetic acid, and etherification reaction is carried out at 50-70°C for 30-70 minutes to obtain a glue solution B containing carboxymethyl cellulose.

[0037] In some embodiments of the present invention, in step Sb-2, the alkalized fiber solution is mixed with chloroacetic acid and subjected to etherification reaction at 52-60° C. for 30-60 min to obtain a glue solution B containing carboxymethyl cellulose.

[0038] In some embodiments of the present invention, step Sb-2 includes: mixing the alkalized fiber solution with chloroacetic acid, performing an etherification reaction at 50-70° C. for 30-70 minutes to generate carboxymethyl cellulose, and adding solvent water to the obtained glue system to obtain glue B containing carboxymethyl cellulose.

[0039] In some embodiments of the present invention, in step Sa-1 and / or step Sb-1, the alcohol solvent includes ethanol.

[0040] In some embodiments of the present invention, in step Sa-1 and / or step Sb-1, the mass ratio of the fiber to the alcohol solvent is (0.01-2):1.

[0041] In some embodiments of the present invention, in step Sa-1 and / or step Sb-1, the alkaline solution comprises a NaOH solution. Optionally, the concentration of NaOH in the NaOH solution is 0.2 to 3 mol / L.

[0042] In some embodiments of the present invention, in step Sa-1 and / or step Sb-1, the mass ratio of the fiber to the alkaline solution is (0.01-2):2.

[0043] In some embodiments of the present invention, in step Sa-1 and / or step Sb-1, the fiber and an alcohol solvent are mixed, immersed at 40-50° C. for 0.5-5 h, an alkaline solution is added, and the mixture is reacted at 40-50° C. for 10-60 min to obtain an alkalized fiber solution.

[0044] In some embodiments of the present invention, in step Sa-2 and / or step Sb-2, the mass ratio of the alkalized fiber solution to chloroacetic acid is (0.5-7):1.

[0045] In some embodiments of the present invention, the negative electrode slurry further comprises an additive. Optionally, the additive comprises a conductive agent and a binder.

[0046] In some embodiments of the present invention, the conductive agent includes but is not limited to one or more of carbon black, acetylene black, carbon nanotubes, graphene, and the like.

[0047] In some embodiments of the present invention, the binder includes but is not limited to one or more of styrene-butadiene rubber, styrene-acrylic emulsion, polyacrylic acid, and the like.

[0048] In some embodiments of the present invention, the negative electrode slurry includes the following components, measured by weight: 85-99 parts of graphite, 1-2 parts of conductive agent, 1-2 parts of binder and 0.5-3 parts of carboxymethyl cellulose.

[0049] In some embodiments of the present invention, the D 50 Particle size slurry D 50 And the particle size of graphite graphite D 99 Graphite D 50 Between: Slurry D 50 ≤(graphite D 99 +Graphite D 50 ) / 2.

[0050] Through the above implementation, the negative electrode slurry has better dispersibility, the conductive agent and other components are dispersed more evenly, the negative electrode obtained by slurry coating is less likely to have defects such as particles and pits, has a high quality rate, and is less likely to experience cycle dives.

[0051] In some embodiments of the present invention, the slurry D 50 12.1~12.6μm, graphite D 99 26.8~27.4μm, graphite D 50 It is 12.1~12.7μm.

[0052] In a second aspect of the present invention, a method for preparing a negative electrode slurry is provided, comprising the following steps:

[0053] S1, mixing graphite with an acid solution to obtain an acid-treated graphite slurry;

[0054] S2, mixing the graphite slurry with carboxymethyl cellulose glue and an additive containing a conductive agent to obtain a negative electrode slurry.

[0055] In some embodiments of the present invention, in step S1, the acid solution comprises an aqueous acid solution.

[0056] In some embodiments of the present invention, in step S1, the acid in the acid solution includes at least one of citric acid, oxalic acid, acetic acid or carbonic acid.

[0057] In some embodiments of the present invention, in step S1, the mass ratio of the acid solution to the graphite is (0.05-0.5):100, such as (0.1-0.15):100, and specifically 0.1:100.

[0058] In some embodiments of the present invention, in the acid solution, the acid concentration is 0.01-0.5 mol / L, such as 0.05-0.08 mol / L, specifically 0.06 mol / L.

[0059] In some embodiments of the present invention, in step S1, graphite is mixed with an acid solution and stirred to obtain an acid-treated graphite slurry.

[0060] In some embodiments of the present invention, in step S1, the stirring time is 5 to 30 minutes, and the stirring speed is 100 to 500 rpm.

[0061] In some embodiments of the present invention, in step S1, a portion of graphite is mixed with an acid solution, and then the remaining portion of graphite is added and stirred to obtain an acid-treated graphite slurry.

[0062] In some embodiments of the present invention, in step S2, the graphite slurry is mixed with a conductive agent, carboxymethyl cellulose glue, and a binder to obtain a negative electrode slurry.

[0063] In some embodiments of the present invention, in step S2, the graphite slurry is mixed with a conductive agent, glue A, glue B and a binder to obtain a negative electrode slurry.

[0064] In some embodiments of the present invention, in step S2, the graphite slurry is mixed with the conductive agent and the glue A, and then the glue B is added and stirred, and the binder is added and stirred to obtain the negative electrode slurry.

[0065] In some embodiments of the present invention, in step S2, the graphite slurry is mixed with the conductive agent and the glue A, stirred at a speed of 100 to 500 rpm for 0.5 to 3 h, and then the glue B is added and stirred at a speed of 100 to 500 rpm for 0.1 to 2 h, and the binder is added and stirred at a speed of 100 to 500 rpm for 0.1 to 2 h to obtain the negative electrode slurry.

[0066] The third aspect of the present invention provides a negative electrode active layer prepared by using the negative electrode slurry.

[0067] According to a fourth aspect of the present invention, a negative electrode is provided, comprising the negative electrode active layer.

[0068] According to a fifth aspect of the present invention, a secondary battery is provided, comprising the negative electrode described above.

[0069] In some embodiments of the present invention, the secondary battery includes at least one of a lithium ion battery or a sodium ion battery. DETAILED DESCRIPTION

[0070] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0071] The experimental methods in the following examples and comparative examples without specifying specific conditions are usually carried out in accordance with conventional conditions in the art or the conditions recommended by the manufacturer; the raw materials and reagents used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Among them, the fiber in Example 1 is natural cellulose, i.e. cotton; the binder solution is styrene-butadiene rubber emulsion with a viscosity of 20 to 100 mPa.s and a solid content of 40%; the conductive agent is carbon black with a tap density of 160 g / cm 3 , specific surface area 60m 2 / g.

[0072] Example 1

[0073] This embodiment discloses a negative electrode slurry, and its preparation process includes the following steps:

[0074] (I) Preparation of glue solution A and glue solution B:

[0075] Preparation of Glue A:

[0076] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, soaked at 45° C. for 2 h, then 2 kg of 1 mol / L NaOH aqueous solution (solvent is deionized water) was added, and reacted at 45° C. for 30 min to obtain an alkaline fiber solution.

[0077] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkaline cellulose solution, and the mixture was reacted at 40° C. for 15 min (etherification reaction) to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue A; wherein the mass fraction of carboxymethyl cellulose in glue A was 2.1%, the degree of substitution Da of carboxymethyl cellulose was 0.65, and the viscosity was 2000 mPa.s.

[0078] Preparation of Glue B:

[0079] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and soaked at 45° C. for 2 h. Then, 2 kg of 1 mol / L NaOH aqueous solution was added and reacted at 45° C. for 30 min to obtain an alkaline fiber solution.

[0080] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkaline cellulose solution, and the mixture was reacted at 55° C. for 45 min (etherification reaction) to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue B; wherein the mass fraction of carboxymethyl cellulose in glue B was 1.0%, the degree of substitution Db of carboxymethyl cellulose was 0.95, and the viscosity was 9000 mPa.s.

[0081] (II) Preparation of negative electrode slurry: wherein the negative electrode slurry is prepared according to the following weight proportions in the negative electrode slurry: 95 parts of graphite, 1.5 parts of conductive agent, 1.5 parts of carboxymethyl cellulose, 2 parts of binder, wherein the mass ratio of glue A to glue B is 2:3, specifically comprising the following steps:

[0082] Stirring steps: first add half of the graphite into the stirring tank, add 0.1% of the total mass of the graphite in a citric acid aqueous solution (the concentration of citric acid in the citric acid aqueous solution is 0.06 mol / L), then add the remaining graphite, premix for 15 minutes, set the speed to 200 rpm, and obtain a mixture M; then add the conductive agent and the glue A, stir for 1 hour, set the speed to 200 rpm, and obtain a mixture N;

[0083] Dispersion step: Add glue solution B to mixture N, stir at 500rpm for 30min to obtain mixture O, and finally add binder solution, stir at 200rpm for 30min to obtain negative electrode slurry. 50 Meet the graphite particle size: slurry D 50 ≤(graphite D 99 +Graphite D 50 ) / 2, where slurry D 50 :12.3μm, graphite D 99 :27.1μm, graphite D 50 :12.5μm.

[0084] This embodiment discloses a negative electrode, including a negative electrode active layer (thickness of 170 μm), which is prepared from the negative electrode slurry of this embodiment. The specific preparation steps include: uniformly coating the negative electrode slurry on a negative electrode current collector copper foil (thickness of 8 μm), and then drying, cold pressing, and striping to obtain a negative electrode.

[0085] Example 2

[0086] The difference between this embodiment and embodiment 1 is that when preparing the negative electrode slurry, carbonic acid is used to replace the citric acid in embodiment 1 in the graphite acid treatment.

[0087] Example 3

[0088] The only difference between this embodiment and embodiment 1 is that when preparing the negative electrode slurry, the concentration of citric acid in the citric acid aqueous solution used for graphite acid treatment is 0.10 mol / L.

[0089] Example 4

[0090] The only difference between this embodiment and embodiment 1 is that when preparing the negative electrode slurry, the concentration of citric acid in the citric acid aqueous solution used for graphite acid treatment is 0.02 mol / L.

[0091] Example 5

[0092] The difference between this embodiment and embodiment 1 is that when preparing the negative electrode slurry, a citric acid aqueous solution with a mass of 0.5% of the total mass of graphite is added during the graphite acid treatment.

[0093] Example 6

[0094] The difference between this embodiment and embodiment 1 is that when preparing the negative electrode slurry, a citric acid aqueous solution with a mass of 0.2% of the total mass of graphite is added during the graphite acid treatment.

[0095] Example 7

[0096] The difference between this embodiment and embodiment 1 is that when preparing the negative electrode slurry, a citric acid aqueous solution with a mass of 0.05% of the total mass of graphite is added during the graphite acid treatment.

[0097] Example 8

[0098] The only difference between this embodiment and embodiment 1 is that in this embodiment, the degree of substitution Da of carboxymethyl cellulose in glue A is 0.70, and the degree of substitution Db of carboxymethyl cellulose in glue B is 0.98, which does not satisfy the relationship: Db=Da+0.3.

[0099] Wherein, the preparation of glue A is:

[0100] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and soaked at 45° C. for 2 h. Then, 2 kg of 1 mol / L NaOH aqueous solution was added and reacted at 45° C. for 30 min to obtain an alkaline fiber solution.

[0101] 2) Etherification: 0.5 kg of chloroacetic acid is mixed with the alkalinized cellulose solution, and the mixture is reacted at 45° C. for 20 min (etherification reaction) to generate carboxymethyl cellulose. Solvent water is added to the obtained glue system to obtain glue A; wherein the mass fraction of carboxymethyl cellulose in glue A is about 2.0%, the degree of substitution Da of carboxymethyl cellulose is 0.70, and the viscosity is about 2000 mPa.s.

[0102] Preparation of Glue B:

[0103] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and soaked at 45° C. for 2 h. Then, 2 kg of 1 mol / L NaOH aqueous solution was added and reacted at 45° C. for 30 min to obtain an alkaline fiber solution.

[0104] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkaline cellulose solution, and the mixture was reacted at 55° C. for 50 min (etherification reaction) to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue B; wherein the mass fraction of carboxymethyl cellulose in glue B was about 0.95%, the degree of substitution Db of carboxymethyl cellulose was 0.98, and the viscosity was about 9000 mPa.s.

[0105] Example 9

[0106] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution A is 500 mpa·s by adjusting the content of deionized water as a solvent in the glue solution.

[0107] Example 10

[0108] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution A is 1000 mpa·s by adjusting the content of deionized water as a solvent in the glue solution.

[0109] Embodiment 11

[0110] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution A is 3500 mpa·s by adjusting the content of deionized water as a solvent in the glue solution.

[0111] Example 12

[0112] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution A is 4000 mpa·s by adjusting the content of deionized water as a solvent in the glue solution.

[0113] Example 13

[0114] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution B is 7000 mpa·s by adjusting the content of deionized water as a solvent in the glue solution.

[0115] Embodiment 14

[0116] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution B is 8000 mpa·s by adjusting the content of deionized water as a solvent in the glue solution.

[0117] Embodiment 15

[0118] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution B is 12000 mpa·s by adjusting the content of deionized water as a solvent in the glue solution.

[0119] Example 16

[0120] The difference between this embodiment and embodiment 1 is that in this embodiment, the viscosity of the glue solution B is 13000 mpa·s by adjusting the content of deionized water as a solvent in the glue solution.

[0121] Embodiment 17

[0122] The difference between this embodiment and embodiment 1 is that the degree of substitution Da of carboxymethyl cellulose in the glue solution A in this embodiment is 0.60. Preparation of glue solution A:

[0123] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and soaked at 45° C. for 2 h. Then, 2 kg of 1 mol / L NaOH aqueous solution was added and reacted at 45° C. for 30 min to obtain an alkaline fiber solution.

[0124] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkalinized cellulose solution, and the mixture was reacted at 40° C. for 10 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue A; wherein the mass fraction of carboxymethyl cellulose in glue A was about 2.2%, the degree of substitution Da of carboxymethyl cellulose was 0.60, and the viscosity was about 2000 mPa.s.

[0125] Embodiment 18

[0126] The difference between this embodiment and embodiment 1 is that the degree of substitution Da of carboxymethyl cellulose in the glue solution A in this embodiment is 0.80. Preparation of glue solution A:

[0127] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and soaked at 45° C. for 2 h. Then, 2 kg of 1 mol / L NaOH aqueous solution was added and reacted at 45° C. for 30 min to obtain an alkaline fiber solution.

[0128] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkalinized cellulose solution, and the mixture was reacted at 45° C. for 25 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue A; wherein the mass fraction of carboxymethyl cellulose in glue A was about 1.9%, the degree of substitution Da of carboxymethyl cellulose was 0.80, and the viscosity was about 2000 mPa.s.

[0129] Embodiment 19

[0130] The difference between this embodiment and embodiment 1 is that the degree of substitution Db of carboxymethyl cellulose in the glue solution B in this embodiment is 0.80. Preparation of glue solution B:

[0131] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and then soaked at 45°C for 2 h. Then, 2 kg of 1 mol / L NaOH solution was added and reacted at 45°C for 30 min to obtain an alkaline fiber solution.

[0132] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkalinized cellulose solution, and the mixture was reacted at 55° C. for 30 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue B; wherein the mass fraction of carboxymethyl cellulose in glue B was about 1.1%, the degree of substitution Db of carboxymethyl cellulose was 0.80, and the viscosity was about 9000 mPa.s.

[0133] Embodiment 20

[0134] The difference between this embodiment and embodiment 1 is that the degree of substitution Db of carboxymethyl cellulose in the glue solution B in this embodiment is 1.20. Preparation of glue solution B:

[0135] 1) Alkalization: 0.5 kg of fiber was first mixed with 1 kg of ethanol, and then soaked at 45°C for 2 h. Then, 2 kg of 1 mol / L NaOH solution was added and reacted at 45°C for 30 min to obtain an alkaline fiber solution.

[0136] 2) Etherification: 0.5 kg of chloroacetic acid was mixed with the alkaline cellulose solution, and the mixture was reacted at 70° C. for 55 min to carry out an etherification reaction to generate carboxymethyl cellulose. Solvent water was added to the obtained glue system to obtain glue B; wherein the mass fraction of carboxymethyl cellulose in glue B was 0.8%, the degree of substitution Db of carboxymethyl cellulose was 1.20, and the viscosity was about 9000 mPa.s.

[0137] Embodiment 21

[0138] The difference between this embodiment and embodiment 1 is that in the step of preparing the glue solution A in this embodiment, the mass fraction of carboxymethyl cellulose contained in the glue solution A is 1.5% by adjusting the original amount of fiber in the alkalization step.

[0139] Embodiment 22

[0140] The difference between this embodiment and embodiment 1 is that in the step of preparing the glue solution A in this embodiment, the mass fraction of carboxymethyl cellulose contained in the glue solution A is 3.5% by adjusting the original amount of fiber in the alkalization step.

[0141] Embodiment 23

[0142] The difference between this embodiment and embodiment 1 is that in the step of preparing the glue solution B in this embodiment, the mass fraction of carboxymethyl cellulose contained in the glue solution B is 0.5% by adjusting the original amount of fiber in the alkalization step.

[0143] Embodiment 24

[0144] The difference between this embodiment and embodiment 1 is that in the step of preparing the glue solution B in this embodiment, the mass fraction of carboxymethyl cellulose contained in the glue solution B is 1.4% by adjusting the original amount of fiber in the alkalization step.

[0145] Comparative Example 1

[0146] This comparative example discloses a negative electrode slurry, which is prepared according to the following substances in parts by weight in the negative electrode slurry: 95 parts of graphite, 1.5 parts of conductive agent, 1.5 parts of carboxymethyl cellulose (CMC), and 2 parts of binder.

[0147] The steps for preparing the negative electrode slurry in this comparative example include:

[0148] (1) Preparation of glue: Add the binder and CMC to part of the deionized water, mix the binder and CMC, then add 0.1% citric acid aqueous solution based on the mass of graphite, mix, and obtain glue solution; the concentration of citric acid in the citric acid aqueous solution is 0.06 mol / L;

[0149] (2) Mixing: mixing graphite and a conductive agent according to the above weight ratio to obtain a mixture;

[0150] (3) kneading: adding 60 wt% of the glue solution in step (1) to the mixed material in step (2), and mixing;

[0151] (4) pulping: adding 20 wt% of the glue solution in step (1) to the product of step (3), adding the remaining deionized water, and mixing;

[0152] (5) Homogenization: Add 20 wt% of the glue solution in step (1) to the product of step (4), mix, and sieve to obtain the slurry with a viscosity of about 4500 mPa.s.

[0153] The rest is the same as Example 1 and will not be described in detail.

[0154] Comparative Example 2

[0155] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode slurry in step (II) of this comparative example: the citric acid aqueous solution, the conductive agent, the glue A, the glue B and the binder are mixed with the graphite at the same time.

[0156] Comparative Example 3

[0157] The difference between this comparative example and Example 1 is that in step (II) of preparing the slurry, glue solution A is used instead of glue solution B in Example 1.

[0158] Comparative Example 4

[0159] The difference between this comparative example and Example 1 is that in step (II) of preparing the slurry, glue solution B is used instead of glue solution A in Example 1.

[0160] Comparative Example 5

[0161] The difference between this comparative example and Example 1 is that no citric acid solution is added in this comparative example, the slurry dispersion is poor, and the slurry D 50 >(Graphite D 99 +Graphite D 50 ) / 2, where slurry D 50 :22.5μm, graphite D 99 :27.1μm, graphite D 50 :12.5μm.

[0162] Comparative Example 6

[0163] The difference between this comparative example and Example 1 is that in the step (II) of preparing the slurry in this comparative example: after the graphite is mixed with other materials, a citric acid aqueous solution is added for mixing.

[0164] Test example

[0165] The negative electrode slurries and batteries obtained in the examples and comparative examples were subjected to performance tests, specifically including:

[0166] Preparation of positive electrode sheets: The positive electrode active material NCM523, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 97:2:1, the solvent NMP is added, and the mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet (coating thickness is 137 μm, positive electrode collector thickness is 12 μm).

[0167] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF 6 Dissolve in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0168] Separator: A polyethylene film (thickness: 12 μm) was selected as the separator.

[0169] Preparation of lithium-ion battery: After winding the above-mentioned positive electrode sheet, separator and negative electrode sheet, liquid injection, packaging and formation are carried out to make a soft-pack battery with a design capacity of 5000mAh, and a design 1C=5000mA; the N / P value is 1.05.

[0170] Test method:

[0171] 1. Use a laser particle size analyzer to test the particle size of the negative electrode slurry after discharge: slurry D 50 ;

[0172] 2. Capacity retention rate: The battery is charged at 1C and discharged at 0.5C at room temperature, with a voltage range of 3.0 to 4.45V, and cycled for 500cls;

[0173] 3. In each embodiment and comparative example, a batch of negative electrode sheets were prepared: the number of defective sheets / the total number of coated sheets is the coating sheet quality rate, and the coating method is extrusion coating.

[0174] Table 1

[0175]

[0176]

[0177] As can be seen from the above table, when only glue A or glue B is used, and the graphite is not treated with acid, the dispersibility of the slurry is poor, and the cycle performance of the resulting battery is poor. Compared with adding too much citric acid (such as Example 5) or too little, adding the preferred citric acid content (adding citric acid aqueous solution is 0.095% to 0.15% of the mass of graphite, such as Example 1) is easier to promote full dispersion, has a better effect on the graphite surface, and is less likely to damage the pH of the entire slurry, thereby being less likely to damage CMC or SBR. Accordingly, directly mixing citric acid and glue without using citric acid to treat graphite first cannot promote the dispersion of the slurry, but will destroy the structure of part of the CMC, resulting in a cycle jump.

[0178] If there is no special explanation, the actual meaning of "about" in the present invention is that the error is allowed within the range of ±2%, for example, about 100 is actually 100±2%×100. The "normal temperature" and "room temperature" in the present invention, if there is no special explanation, are about 20-30°C. The "between" in the present invention includes the number itself, for example, "between 2-3" includes the endpoint values ​​2 and 3.

[0179] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A negative electrode slurry, characterized in that: The invention comprises acid-treated graphite and carboxymethyl cellulose glue, wherein the carboxymethyl cellulose glue comprises glue A and glue B, the viscosity of glue A is 500-4000 mpa·s, and the viscosity of glue B is 7000-13000 mpa·s.

2. The negative electrode slurry according to claim 1, characterized in that Satisfies at least one of the following (1) to (7): (1) The viscosity of the glue A is 1000-3500 mPa·s, and the viscosity of the glue B is 8000-12000 mPa·s; (2) The degree of substitution Da of carboxymethyl cellulose in the glue A is 0.6 to 0.8, and the degree of substitution Db of carboxymethyl cellulose in the glue B is 0.8 to 1.2; (3) The degree of substitution Da of carboxymethyl cellulose in the glue A and the degree of substitution Db of carboxymethyl cellulose in the glue B satisfy: Db = Da + 0.3; (4) The mass fraction of carboxymethyl cellulose contained in the glue A is 1.5% to 3.5%; (5) The mass fraction of carboxymethyl cellulose contained in the glue B is 0.5% to 1.4%; (6) In the negative electrode slurry, the mass ratio of the glue solution A to the glue solution B is (3-7):(3-7); (7) In the negative electrode slurry, the weight ratio of graphite to carboxymethyl cellulose is (85-99):(0.5-3).

3. The negative electrode slurry according to claim 1, characterized in that: The acid used in the acid treatment includes at least one of carboxylic acid and carbonic acid; Preferably, the acid used in the acid treatment includes at least one of citric acid, oxalic acid, acetic acid and carbonic acid.

4. The negative electrode slurry according to claim 1, characterized in that: The acid treatment step comprises: mixing graphite with an acid solution and stirring to obtain the acid-treated graphite; Preferably, the acid solution comprises an aqueous solution of an acid; Preferably, the mass ratio of the acid solution to graphite is (0.05-0.5):100; Preferably, in the acid solution, the acid concentration is 0.01-0.5 mol / L.

5. The negative electrode slurry according to claim 1, characterized in that: The glue solution A is prepared by a preparation method comprising the following steps: Sa-1, mixing the fiber and an alcohol solvent, and mixing with an alkaline solution to obtain an alkalized fiber solution; Sa-2, the alkalized fiber solution is mixed with chloroacetic acid, and etherification reaction is carried out at 30-45°C for 10-30 minutes to obtain a glue solution A containing carboxymethyl cellulose; And / or, the glue solution B is prepared by a preparation method comprising the following steps: Sb-1, mixing the fiber and an alcohol solvent, and mixing with an alkaline solution to obtain an alkalized fiber solution; Sb-2, alkalized fiber solution is mixed with chloroacetic acid, and etherification reaction is carried out at 50-70°C for 30-70 minutes to obtain glue solution B containing carboxymethyl cellulose; Preferably, in step Sa-1 and / or step Sb-1, the alcohol solvent comprises ethanol; Preferably, in step Sa-1 and / or step Sb-1, the mass ratio of the fiber to the alcohol solvent is (0.01-2):1; Preferably, in step Sa-1 and / or step Sb-1, the alkaline solution comprises a NaOH solution; Preferably, in step Sa-1 and / or step Sb-1, the mass ratio of the fiber to the alkaline solution is (0.01-2):2; Preferably, in step Sa-1 and / or step Sb-1, the fiber and the alcohol solvent are mixed, immersed at 40-50° C. for 0.5-5 h, an alkaline solution is added, and the mixture is reacted at 40-50° C. for 10-60 min to obtain an alkalized fiber solution.

6. The negative electrode slurry according to claim 1, characterized in that: The negative electrode slurry has a D 50 Particle size slurry D 50 And the particle size of graphite graphite D 99 Graphite D 50 Between: Slurry D 50 ≤(graphite D 99 +Graphite D 50 ) / 2.

7. A method for preparing a negative electrode slurry, characterized in that: The steps include: S1, mixing graphite with an acid solution to obtain an acid-treated graphite slurry; S2, mixing the graphite slurry with carboxymethyl cellulose glue and an additive containing a conductive agent to obtain a negative electrode slurry; Preferably, in step S2, the graphite slurry is mixed with a conductive agent, carboxymethyl cellulose glue and a binder to obtain a negative electrode slurry.

8. A negative electrode active layer, characterized in that: The negative electrode slurry is prepared by using the negative electrode slurry, wherein the negative electrode slurry includes the negative electrode slurry according to any one of claims 1 to 6 or the negative electrode slurry prepared by the preparation method according to claim 7.

9. A negative electrode, characterized in that Comprising the negative electrode active layer as claimed in claim 8.

10. A secondary battery, characterized in that: Comprising the negative electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Method for producing electrode slurry for lithium ion secondary battery

    CN101641812A

  • Negative electrode paste of lithium battery and preparation method of negative electrode paste

    CN113363485A

  • Graphite negative electrode material with electrolyte universality and preparation method and application thereof

    CN113526502A

  • Sodium-ion battery negative electrode slurry preparation method and sodium-ion battery

    CN116454233A

  • Preparation method of lithium ion battery negative plate and application of lithium ion battery negative plate in lithium ion battery

    CN117613201A